Cita Rasa, Harga, dan Tingkat Penghasilan Konsumen : Analisis Moderasi terhadap Keputusan Pembelian Rokok di Kota Malang - Cornelia Angelina P.H; Mulyono Mulyono; Dharmayanti Pri Handini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study also provides insight into how external factors, such as price and taste, can be key determinants in consumer purchasing decisions, which are heavily influenced by personal preferences and individual economic conditions. Excessively high prices can reduce consumer purchasing power, especially in low-income market segments, potentially reducing sales volume. Conversely, flavors that suit consumer preferences will encourage repeat purchases. Therefore, companies must consider competitive pricing while maintaining distinctive flavors to attract consumer loyalty. Furthermore, income level, as a moderating variable, plays a crucial role in determining purchasing decisions. Consumers with higher incomes tend to have greater freedom in choosing products based on quality and taste without paying too much attention to price. Conversely, consumers with lower incomes prefer to consider price as the primary factor in purchasing decisions. This suggests that pricing strategies must be tailored to the target market segment, both in terms of purchasing power and sensory preferences. The findings of this study are highly relevant for marketers seeking to design effective marketing campaigns, particularly in consumer product industries such as cigarettes. By understanding the influence of taste, price, and income levels, companies can more carefully determine appropriate prices and offer products that meet consumer preferences. Therefore, this research can guide companies in developing marketing strategies based on a deeper understanding of consumer behavior. The findings also suggest the importance of deeper market segmentation to identify consumer preferences based on income levels and other economic factors.